Application of Finger Paint to Stimulate Fine Motor Development in Preschool Children - Ika Maelany; Tri Sakti Widyaningsih (Journal of Language and Health, 2022)
In general, pre-school age is a time for children with the achievement of their independent activities, children also begin to master various physical skills and courage, usually this condition is influenced by gross motor and fine motor development. Fine motor development needs to be understood especially at the beginning of the development period, namely childhood so that this fine motor can be considered important to know the extent of the child's development. One of the activities that can be done to develop fine motor skills is finger painting. Finger painting is a finger painting activity that is carried out by scraping dye directly with the fingers of the hand, palm freely on paper, this child can explore free ideas to develop his fine motor skills. The purpose of this study is to determine the application of finger painting learning applied by parents of children during learning assistance at home in developing Fine Motor Skills of Pre-School children. Purpose to find out the application of finger painting learning applied by parents of children during learning assistance at home in developing Fine Motor Skills of Pre-School children. The type of research used is a quantitative method with a case study approach with a total of 5 subjects through observation and interviews. The instruments used are observation sheets and SOPs with descriptive analysis. The inclusion criteria are children aged 3-5 years, parents allow children to be subjects, children in healthy and cooperative conditions, while the exclusion criteria are subjects that are not in the implementation of case studies. The results of most children developing very well as many as 2 people and undeveloped as many as 2 people. While the child who develops according to expectations there is 1 person. Finger painting activities can be useful for stimulating children's fine motor aspects because by doing finger painting activities children can move their fingers so that they involve the movement of small muscles and nerve maturity.